B19 The Wnt Receptor Ryk Reduces Neuronal Resistance Capacity By Repressing Foxo Activity During The Early Phases Of Huntingtin Pathogenicity. (17th September 2014) - Tourette, C; Farina, F; Vazquez-Manrique, RP; Orfila, AM; Voisin, J; Hernandez, S; Offner, N; Parker, JA; Menet, S; Kim, J; Lyu, J; Choi, SH; et al.
Abstract : Background: The ability of neurons to cope with the chronic stress induced by mutant protein expression in Huntington's disease (HD) may determine the course of their decline and eventual demise. Although the pathophysiological importance of stress response has been previously shown in HD, very little is known about the pathways that regulate the overall capacity of neurons to maintain function during the early phases of mutant huntingtin (Htt) pathogenicity. Aim and method: We used several models of HD to investigate the links between neurodevelopmental and stress response pathways in HD. More precisely, we explored the possibility that Wnt/Ryk signalling, which is important for neurogenesis, might regulate FOXO activity in HD, as suggested by network-based analysis of microarray data from purified C. elegans neurons expressing human polyQ-Htt. Outcome: We found that the Wnt receptor Ryk, a protein important for axon guidance, is increased in several models of HD, which may occur prior to or during the early phases of the disease process as suggested by C. elegans and mouse models of HD. Interestingly, increased levels of Ryk repress activity of the FOXO proteins, a family of transcription factors that play an important role in cell survival/longevity and neuronal homeostasis and protection. Ryk directly represses FOXO protective activity through its intracellular domain, a γ-secretase cleavage product previously implicated in cortical neurogenesis. This highlights the regulation of HD neuron survival by a Ryk pathway that is distinct from canonical Wnt/Ryk signalling. Conclusion: From our findings, we postulate that neurons are unable to develop an efficient FOXO-mediated survival response during the very early phases of the pathogenic process in HD. This suggest that restoring FOXO-mediated stress response has significant therapeutic potential and that FOXO-interaction networks might contain important indicators of drug protection. Support: ANR, CHDI Foundation, HDF, Inserm, Association Huntington France, AFM, AP-HP, Bumpus Foundation, NIH, Veterans administration.